Peran Manajerial Kyai dalam Peningkatan Sarana dan Prasarana Pendidikan di Pondok Pesantren Al-Furqon Cimerak - Taufik Hidayat (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2025)
Al-Furqon Cimerak Islamic Boarding School is one of the religious educational institutions that plays an important role in shaping the character and knowledge of students. Despite having a strong educational tradition, this Islamic boarding school faces significant challenges related to adequate educational facilities and infrastructure. Suboptimal facilities and infrastructure can hinder the teaching and learning process and affect the overall quality of education. This research aims to examine the role of kyai in improving educational facilities and infrastructure at the Al-Furqon Cimerak Islamic Boarding School. Kyai as leaders of islamic boarding school have an important role in developing facilities that support teaching and learning activities or recitation. This research uses a qualitative approach with a case study method. Data was collected throught interviews, observation and documentation involving yai, santri and islmic boarding school managers. The results of this research show that Kyai have a central role in managing facilities and infrastructure, which includes planning, organizing, implementing and supervising. Kyai also plays a role in building partnerships with the community and alumni to support the development of educational facilities. This research concludes that good management by Kyai contributes significantly to improving the quality of education at the Al-Furqon Cimerak Islamic Boarding School. As a recommendation, management training is needed for Kyai and administrators, as well as increased participation of students in maintaining facilities. It is hoped that these steps can strengthen the foundation of education in Islamic boarding schools.